Pengaruh Other Comprehensive Income (OCI) terhadap Manajemen Laba pada Perusahaan Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2023–2025 - Yosep Eka Putra; Mega Rahmi; Sonia Andari; Yona Amelia Agustin; Sherlina Yudistira; Syarifa Ainul Yaqin (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effect of Other Comprehensive Income (OCI) on earnings management in consumer cyclicals companies listed on the Indonesia Stock Exchange for the 2023–2025 period. The study used quantitative methods with secondary data in the form of financial statements and annual reports. The sample was selected using a purposive sampling technique, obtaining 42 observational data after filtering and removing outliers. OCI was used as the independent variable, while earnings management was measured using discretionary accruals using the Modified Jones Model approach. The analysis was conducted using classical assumption tests and simple linear regression. The results showed that OCI had no significant effect on earnings management, with a t-test significance value of 0.680 (>0.05). The R Square value of 0.004 indicates that OCI only explains 0.4% of changes in earnings management, with the remainder being influenced by other factors. Thus, OCI is not the primary factor influencing earnings management practices in consumer cyclical companies listed on the IDX during the 2023–2025 period.